Leadership in Action: Staying on Track: How to Keep in Touch with Your Development Progress - Hannum, Kelly; Hoole, Emily (Center for Creative Leadership, 2009)
Devising a developmental goal and efficiently tracking your progress toward the goal require articulating your goal, creating an action plan, gathering information about your behavior, identifying barriers and supports, and revising your action plan. Following these steps will greatly enhance your chances of reaching your goal.
Keywords: Career development; Plan de carrière